Hočevarica Eneolitsko kolišče na Ljubljanskem barju = An eneolithic pile dwelling in the Ljubljansko barje - Velušček, Anton (Opera Instituti Archaeologici Sloveniae, 2004)
The monograph presents the entire course of archaeological and dendrochronological investigations of two pile dwelling cycles at the Hočevarica site in the Ljubjansko barje, which occurred approximately in the 37th and the first half of the 36th century BC.In addition to artefacts from Hočevarica (A. Velušček), the results from paleobotanical investigations (M. Jeraj), a classification of the material from a necklace ring (D. Skaberne and A. Mladenovič), analyses of metallurgic instruments (Ž. Šmit) as well as organic remains of mammals (B. Toškan and J. Dirjec), fish (M. Govedič, J. Pavšič and J. Dirjec) and birds (F. Janžekovič and V. Malez) are also presented.